Penguatan Peran Dewan Pertahanan Nasional (DPN) melalui Pemberdayaan Jabatan Fungsional Analis Pertahanan Negara (APN): Analisis Kualitatif Asosiatif - Pratondo Ario Seno Sudiro (Badan Pendidikan dan Pelatihan Kementerian Pertahanan, 2025)
Defense is a primary ideal of Indonesia, as articulated in the Preamble to the 1945 Constitution. The Constitution also affirms that Indonesia is a state founded on popular sovereignty. From the relation of national defense and popular sovereignty emerged the notion of a Total Defense System (Sishanta). To implement this system, the National Defense Council (DPN) was established. As an institution responsible for formulating and establishing strategic policies, the DPN requires personnel with expertise in national defense analysis. Meanwhile, a functional position of National Defense Analyst (APN) exists with the mandate to analyze national defense issues in order to support the national defense system. However, as of 2024, no APN functional position has been included in the CPNS formations of either the Ministry of Defense of the Republic of Indonesia (Kemhan RI) or the DPN. Starts from the gap, this study aims to analyze form of the relationship between the empowerment of APN functional positions and the existence of the DPN. It employs an associative qualitative approach, using data from direct observation and literature study, then analyzed through the Miles and Huberman method. The study results mainly that a harmonious relationship exists because both the APN functional positions and the DPN share closely related job responsibilities. Therefore, it recommends that the Indonesian Ministry of Defense open positions for First Expert and Junior Expert APN functional roles in the upcoming CPNS recruitment to enable the DPN to fulfill its duties and functions effectively.